(untitled) (Al-Academy, 2019)
The contemporary arts, including the graphic design art, adopted new concepts and methods that diverged from the customary rules of design, such as the method of irregularity, as a result of the art keeping up with the intellectual, scientific and technical developments that accompanied all fields of life which caused a problem in employing this technique because of its influence on the functional aspect of the graphic achievement. Hence, the researcher chose the title of the research entitled (the irregularity in contemporary graphic achievement) based on the following questions: a-Does the transformation of style in contemporary graphic design constitute a problem for the designs it produces?b- Has the contemporary graphic design achieved its aesthetic dimensions through the irregularity method? The theoretical framework included four sections as follows: The first section is the irregularity in the philosophy of art, and the second section is the irregularity in design and the third one is the irregularity through the elements of design and the fourth section included the techniques of the artistic direction of the graphic achievement, then the research procedures included the analysis of the research sample. The most important findings and conclusions were as follows:A - The method of irregularity is one of the contemporary technical methods that have made a big-time change in the construction of contemporary graphic design and added an aesthetic and functional dimension to the modern design system.B - The method of the irregularity adopted the mechanism of innovation in dealing with the design elements being influential design forces capable of violating the design system, as well as technological developments that contributed to the formulation of these elements and influence them in an unusual way.